CONDITIONED MORPHINE WITHDRAWAL ELICITED BY ENVIRONMENTAL AND PHARMACOLOGICAL CUES - McDonald, Robert V. (My University, 2001)
Many studies have demonstrated the important contribution of Pavlovian conditioning to the phenomena of drug tolerance and withdrawal. In the Pavlovian analysis, cues that are paired with drug administration come to elicit compensatory responses in anticipation of the subsequent drug-induced physiological disturbance. Furthermore, when such cues are presented in the absence of the drug, the compensatory conditional responses elicited by the drug- paired cues are evident as withdrawal behaviors. The present experiments investigate the validity of both commonly used and novel behavioral indices of morphine withdrawal in the rat model. The results suggest that rearing may not be a valid behavioral index of withdrawal, and that mouth movements may be a sensitive and valid index. The present experiments also investigate the types of stimuli that can serve as effective cues for drug administration. While past studies of conditioned morphine withdrawal have typically employed external environmental stimuli as cues, recent research has suggested that internal pharmacological cues inherent in the drug administration itself may, in some circumstances, come to control the expression of tolerance and withdrawal behaviors. The results of these experiments show that rats conditioned with a high dose of morphine display more withdrawal behaviors when given a small dose of morphine than when given a placebo injection. This result is interpreted as evidence that the early effects of a large dose of a drug, reproduced by the administration of a small dose of the drug, can serve as conditional stimuli and elicit compensatory conditional responses. The finding that morphine withdrawal can be elicited by administration of morphine has implications for a wide range of issues in drug tolerance, withdrawal, and dependence.
CONDITIONED MORPHINE WITHDRAWAL
Keywords: Morphine Withdrawal; Pavlovian Conditioning; Physiology; Behaviour; Tolerance; Dependence